Evaluation of the cardiovascular effects of varenicline in rats - Selçuk EB; Sungu M; Parlakpinar H; Ermiş N; Taslıdere E; Vardı N; Yalçınsoy M; Sagır M; Polat A; Karatas M; Kayhan-Tetik B (Dove Medical Press, 2015)
Engin Burak Selçuk,1 Meltem Sungu,2 Hakan Parlakpinar,3 Necip Ermiş,4 Elif Taslıdere,5 Nigar Vardı,5 Murat Yalçinsoy,6 Mustafa Sagır,3 Alaaddin Polat,7 Mehmet Karatas,8 Burcu Kayhan-Tetik11Department of Family Medicine, 2Inonu University Medical Faculty, Malatya, Turkey; 3Department of Pharmacology, 4Department of Cardiology, 5Department of Histology and Embryology, 6Department of Pulmonary Medicine, 7Department of Physiology, 8Department of Medical Ethics, Inonu University Medical Faculty, Malatya, TurkeyBackground: Cardiovascular disease is an important cause of morbidity and mortality among tobacco users. Varenicline is widely used worldwide to help smoking cessation, but some published studies have reported associated cardiovascular events.Objective: To determine the cardiovascular toxicity induced by varenicline in rats.Materials and methods: We randomly separated 34 rats into two groups: 1) the control group (given only distilled water orally, n=10) and the varenicline group (given 9 µg/kg/day varenicline on days 1–3, 9 µg/kg twice daily on days 4–7, and 18 µg/kg twice daily on days 8–90 [total 83 days], n=24). Each group was then subdivided equally into acute and chronic subgroups, and all rats in these groups were euthanized with anesthesia overdose on days 45 and 90, respectively. Body and heart weights, hemodynamic (mean oxygen saturation, mean blood pressure, and heart rate, electrocardiographic (PR, QRS, and QT intervals) biochemical (oxidants and antioxidants), and histopathological analyses (including immunostaining) were performed.Results: Acute varenicline exposure resulted in loss of body weight, while chronic varenicline exposure caused heart weight loss and decreased mean blood pressure, induced lipid peroxidation, and reduced antioxidant activity. Both acute and chronic varenicline exposure caused impairment of mean oxygen saturation. QT interval was prolonged in the chronic varenicline group, while PR interval prolongation was statistically significant in both the control and acute varenicline groups. Caspase-9 activity was also significantly increased by chronic exposure. Moreover, histopathological observations revealed severe morphological heart damage in both groups.Conclusion: Adverse effects of chronic varenicline exposure on cardiovascular tissue were confirmed by our electrocardiographic, biochemical, and histopathological analyses. This issue needs to be investigated with new experimental and clinical studies to evaluate the exact mechanism(s) of the detrimental effects of varenicline. Physicians should bear in mind the toxic effects of varenicline on the cardiovascular system when prescribing it for smoking cessation.Keywords: varenicline, smoking, cardiovascular, rat, electrocardiogram, histopathological evaluation